Resveratrol alleviates oxygen/glucose deprivation/reoxygenation-induced neuronal damage through induction of mitophagy - Ye, Ming (Mol Med Rep, 2021)
Resveratrol confers neuroprotective effects in cerebral ischemia; however, the involvement of mitophagy in the neuroprotective function of resveratrol remains unclear. The aim of the present study was to investigate whether resveratrol exerts neuroprotective effects on primary cortical neurons subjected to oxygen/glucose deprivation/reoxygenation (OGD/R) via modulating mitophagy. The data demonstrated that resveratrol at 1–10 µM during reoxygenation improved cell viability and suppressed apoptosis following OGD/R in a concentration-dependent manner. Moreover, resveratrol alleviated OGD/R-induced loss of mitochondrial membrane potential and excessive oxidative stress. Confocal imaging of LC3 and TOM20 antibody-labeled mitochondria, as well as western blot analysis, demonstrated that mitophagy was further enhanced following resveratrol treatment. In addition, resveratrol was revealed to stimulate the phosphatase and tensin homolog-induced kinase 1/Parkin pathway. Mitophagy inhibition then inhibited the protective effects of resveratrol. These results indicated that resveratrol exerts its protective effects against OGD/R damage, at least in part, by promoting mitophagy.